Management of mechanical ventilators in intensive care unit patients from a nursing perspective - Debora Vitória Maria de Souza Florencio; Heitor Bezerra do Nascimento; Vivianne Soares Domingos da Silva; Maria da Conceição Cavalcanti de Lira; Augusto Cesar Barreto Neto; Milton Cezar Compagnon (Nursing and Health Sciences Journal (NHSJ), 2025)
The Intensive Care Unit (ICU) requires continuous monitoring and advanced technologies, such as mechanical ventilation, to support critically ill patients. Proper management of this resource is essential for the quality of care provided. This study aims to evaluate managing patients undergoing mechanical ventilation in an intensive care unit. This cross-sectional, quantitative prevalence study involves nursing professionals working in adult intensive care units at the Hospital das Clínicas of the Federal University of Pernambuco, in Recife, Brazil. Data collection was carried out through three questionnaires: the first consisted of sociodemographic data of the participants, while the second and third were developed based on the sector’s Standard Operating Protocol for mechanical ventilation and COFEN Resolution No. 639/2020, respectively. ICU nurses demonstrated a prevalence of good knowledge about mechanical ventilation of 28% (95% CI: 10.4-45.6), with a higher prevalence of women (84.0%) compared to men (16.0%). The prevalence of good knowledge regarding Resolution 639/2020 was 52% (95% CI: 33.5-70), while 48% of the nurses showed poor knowledge. Regarding skin color, 69.2% of Black and Brown nurses demonstrated good ethical knowledge, while 30.8% had regular or poor knowledge. The results of this study indicate that nurses' proficiency in managing mechanical ventilators and patients remains inadequate.